Crystallographic orientation dependence of hydrogen-induced cracks in single-crystalline CrCoNi medium-entropy alloy - Yang, Dae Cheol; Zargaran, Alireza; Trang, Thi Thanh Tram; Song, Sang Yoon; Baek, Ju-Hyun; Lee, Jungwan; Seo, Seong-Moon; Kim, Young Kyun; Suh, Jin-Yoo; Kim, Hyoung Seop; Na, Young Sang; Sohn, Seok Su (Elsevier Editora Ltda, 2024)
The mechanical properties of materials, especially metals and alloys, can be significantly enhanced through deformation-induced twin strengthening. This phenomenon is intrinsically tied to microstructural factors, such as stacking fault energy, yield strength, crystallographic orientation, and grain size. The role of twinning in increasing hydrogen embrittlement (HE) resistance, however, has been a subject of varying research outcomes. This study aims to systematically validate the interactions between twinning and hydrogen in a controlled electrochemical environment, focusing on the single-crystalline CrCoNi medium-entropy alloy. Employing a single-crystalline CrCoNi alloy excludes the potential influences of grain boundary and texture, allowing for a clear investigation of the relationship between deformation structure and hydrogen. Four distinct tensile directions were deliberately selected based on crystallographic orientations within the stereographic triangle, revealing variations in twin structure evolutions. In the twin-oriented deformed tensile directions, a significant reduction in ductility became evident due to the presence of deformation twins. However, variations in HE susceptibility in each tensile direction occurred as a consequence of the evolution of deformation twin structures and their interactions with slip. The underlying mechanism revealed that the twin transmission profoundly affects HE susceptibility. This research features the intricate interplay of twinning and hydrogen, emphasizing the necessity of understanding these mechanisms for optimizing FCC structural materials.